Reconstructing Legal Regulation Of Battery Electric Vehicles For Sustainable Development In Indonesia - Wirawan, I Nyoman Arta; Budiartha , I N Putu; Rideng, Wayan (PT Keberlanjutan Strategis Indonesia, 2026)
This article examines legal certainty challenges in Indonesia's battery electric vehicle regulation and proposes a reconstruction to better align governance with sustainable development. The study uses normative legal Research employing statutory and conceptual approaches, focusing on the existing regulatory framework and relevant legal principles. The analysis finds that current regulation still contains vague norms and regulatory gaps, particularly egarding enforceable obligations for business actors, producer responsibility across the battery life cycle, battery waste governance, oversight mechanisms, inter-institutional coordination, and the effectiveness of sanctions. These weaknesses may reduce legal certainty, undermine accountability, and lead to inconsistent implementation across sectors and levels of government. The study interprets these findings as indicating the need to strengthen the regulatory design by introducing clearer, binding norms that integrate environmental accountability and fair transition considerations, supported by measurable compliance duties and effective enforcement mechanisms. The article concludes that legal reconstruction is essential to ensure a consistent, accountable, and sustainable pathway for Indonesia's national battery-electric vehicle ecosystem.